An amendment and extension of tide gauge data analysis for Churchill, Manitoba - Barnett, D. M. (Canadian Journal of Earth Sciences, 1970)
An amended rate of land emergence at Churchill, Manitoba is given as 1.3 ft (39 cm) per century with 95% confidence limits of 1.68 ft and 0.85 ft (51.2 and 25.9 cm). It is based on a polynomial regression analysis of tide gauge data for 1940–1968 using the linear function as the most satisfactory.